Local, northern, material and aesthetic knowing in craftivism - Huhmarniemi, Maria (2022)
In this presentation, I create a visual narrative of my artistic research in which I try to renew, Finnish traditions and cultural heritage, as well as raise awareness and discussion of cultural policies, identities and conflicts. I describe my art as craftivism: part of an international artistic movement in which embroidery, crocheting, knitting and similar textile crafts are used in conversations about uncomfortable issues. Colour combinations, specific qualities of yarn, and decorative patterns give local character to mittens, cardigans, and other knits. In many regions, patterns have a communicative function: they carry cultural symbols and representations of cultural identities. In my craftivism, these regional elements have a communicative role. In this presentation, I describe artistic productions that have included participatory methods and the use of patterns as visual communication. The study follows the approach of art-based action research in which cultural revitalisation and Arctic pride is promoted. I consider how artists and crafters can continue, revitalise and share tactile, material and cultural knowledge. My focus is on the contemporary Arctic.